Kinematic analysis of the biomechanics of Chinese male race walkers - Shi, Y.; Jiang, L. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: Race walking is a traditional and prominent event in China, in which athletes could have a high potential to achieve world medal status. The modification of the Regulations of race walking has had a large influence on the event. Many Chinese race walking athletes have been penalized several times. This situation suggests that the international race walking judges are unable to approbate the Chinese biomechanical characteristics associated with this event. With the 2008 Olympic Games being held in Beijing, it is important to uncover the biomechanical and technical traits of the athletes who are incurring these penalties. Methods The athletes` techniques were analyzed using close-range dynamic stereo photography, threedimensional Kinetic analysis and mathematical statistics were carried out on the results. In addition, a comprehensive review of the literature was performed. Results It was found that Chinese athletes` average stride length was 1.162m, which is shorter than that of most athletes from other nations. Furthermore, the average stride frequency of the Chinese athletes` was 3.515 paces/second indicating Chinese race walkers have a higher static frequency average for overseas athletes. It was also established that the average transit time of these athletes is 54m/s, the average speed of the center of gravity was 4.970 m/s, with the extent of fluctuation being 7.225cm. The extent of rotation of coxa was found to be 40.530 º and the pitch angle of Chinese athletes` trunk averaged at 6.12º .The touchdown angles of left and right feet were 63.66 ºand 64.84 º respectively, while the average angle of knee joint of supporting leg at the moment of touchdown was 173.816 º. Discussion / Conclusions The findings suggest that owing to a shorter stature of Chinese athletes, the stride length is shorter and the stride frequency is higher. These factors result in a decreased speed of the center of gravity compared to the overseas athletes. This finding serves as a biomechanical reason why the achievements of Chinese athletes in this event are not of the same standard as some overseas athletes. It was also concluded that the transit time of Chinese athletes is elongated due to a large extent of fluctuation of the body`s center of gravity; consequently, lowering the speed of the plane. Furthermore, the agility of the athletes` coxa is compromised, which directly shortens the stride length. In addition to this, the pitch angle and touchdown angles of the athletes` feet are too large. The technicalities of the supporting leg in the phase of touchdown are also poor; the unbent stance of this leg is easily seen as a penalty by the judges.